Coupling quaternary ammonium surfactants to the surface of liposomes improves both antibacterial efficacy and host cell biocompatibility - Montefusco-Pereira, Carlos; Formicola, Beatrice; Goes, Adriely; Re, Francesca; Marrano, Claudia A.; Mantegazza, Francesco; Carvalho-Wodarz, Cristiane; Fuhrmann, Gregor; Caneva, Enrico; Nicotra, Francesco; Lehr, Claus-Michael; Russo, Laura (European Journal of Pharmaceutics and Biopharmaceutics, 2020)
By functionalizing the surface of PEG-liposomes with linkers bearing quaternary ammonium compounds (QACs), we generated novel bacteria disruptors with anti-adhesive properties and reduced cytotoxicity compared to free QACs. Furthermore, QAC-functionalized liposomes are a promising platform for future drug encapsulation. The QAC (11-mercaptoundecyl)-N,N,N-trimethylammonium bromide (MTAB) was attached to maleimide-functionalized liposomes (DSPE-PEG) via thiol linker. The MTAB-functionalized liposomes were physicochemically characterized and their biological activity, in terms of anti-adherence activity and biofilm prevention in Escherichia coli were assessed. The results showed that MTAB-functionalized liposomes inhibit bacterial adherence and biofilm formation while reducing MTAB toxicity.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Anti-adherence nanoparticles; Bacterial biofilm; Liposomes; Quarternary ammonium functionalization